Model dan Implementasi Putusan Mahkamah Konstitusi dalam Pengujian Undang-Undang (Studi Putusan Tahun 2003-2012) - Asy’ari, Syukri; Hilipito, Meyrinda Rahmawaty; Ali, Mohammad Mahrus (Mahkamah Konstitusi Republik Indonesia, 2013)
Research concerning model and implementation of Constitutional Court Verdicts in Judicial Review of Law against the 1945 Constitution constitutes juridical normative research using secondary data which is primary legal material namely Constitutional Court verdicts issued from 2003 until 2012. This research aimed at identifying decisions of which the dictum say it granted the petition submitted at the Court so that a comprehensive and integrative description of the model and implementation of Constitutional Court verdict can be found out. Article 56 Paragraph (3) and Article 57 Paragraph (1) of Law No. 24 Of 2003 as amended with Law No. 8 of 2011 on the Amendment of Law on Constitutional Court stipulate that in case a petition is granted, the Court will, at the same time, declares that a law is contradictory to the 1945 Constitution either wholly or partially and legally null and void since declard in an open court. This research found out that there are other models of verdict with their own characteristics. Condititonally constitutional and conditionally unconstitutional verdict is basically a model of decisions which do not legally nullify and declare a norm null but these two models contain interpretation of a content of a paragraph, an article and/or part of a law or the whole part of a law which is basically declared contradictory or not contradictory to the Constitution and still have the force of law or do not have the force of law. A limited constitutional model of verdict which postpone an enforcement of a decision which basically aims at providing some time for transition of the provision which has been declared contradictory to the constitution to remain in force until a certain time in the future. Another model of verdict is a decision which formulate a new norm in order to cope with the unconstitutionality of implementation of a norm. This new norm is temporary in nature and will be included in the new law or revision of related law. The implementation of Constitutional Court decision can be inferred from the model of the decisions. A self-executing force can generally be applied to a legally null and void model of verdict and a model of verdict which formulates new norms. Conditionally constitutional, conditionally unconstitutional and limited constitutional model of verdict is non self-executing. This models must go through legislation process either with revision of laws or making of new laws and regulation process for the ordinances made under any acts.